2020
DOI: 10.1039/d0cp04659k
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive stability of a free-standing monolayer clay mineral nanosheet via transmission electron microscopy

Abstract: Among 2D materials, clay mineral nanosheets have been extensively studied owing to their specific features, such as high surface charge and large surface area. Recently, we reported a stable free-standing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…They reported that high temperature and pressure were required as high-energy sources to separate the layers. Additionally, Akita and co-workers 22 and Brito et al 23 found that centrifugation and annealing processes were necessary to achieve a single-layered clay. Clearly, perfect exfoliation methods are poorly understood, although several mechanisms have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that high temperature and pressure were required as high-energy sources to separate the layers. Additionally, Akita and co-workers 22 and Brito et al 23 found that centrifugation and annealing processes were necessary to achieve a single-layered clay. Clearly, perfect exfoliation methods are poorly understood, although several mechanisms have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the bright contrast of the Pt atoms, the clay mineral nanosheets were observed stably and exhibited the characteristic periodic hexagonal contrast pattern of pristine clay mineral nanosheets. 21,22 These observations demonstrated that Pt atoms are a valid marker for ADF−STEM imaging of guest molecules assembled on a clay mineral nanosheet, as well as on simpler substrates such as graphene. [13][14][15] The Fourier transform (Figure 3d) corresponding to the medium magnification ADF-STEM image of the monolayer region (Figure 3c) revealed that the in-plane distance was similar to previously reported values for the (hk0) facet of montmorillonite.…”
Section: Resultsmentioning
confidence: 91%
“…Stable atomic-scale imaging of monolayer clay mineral nanosheets via ADF-STEM was recently reported for the first time by the current authors. 21,22 The present study aimed to directly image single organic molecules and supramolecular assemblies on monolayer clay mineral nanosheets using heavy metal atom markers. Electrostatic interactions are a weak non-covalent interaction, and enabled strong fixation of each organic molecule on the ionic 2D nanosheet supports.…”
Section: Introductionmentioning
confidence: 99%
“…The observed in-plane distances for 2D VMT are shown in Table S1 (Supporting Information) and consistent with the atomic structure expected for monoclinic alluminosilicates. [27,28] Energy-dispersive X-ray spectroscopy maps of 2D VMT show the presence of Si, Al, Mg, and Fe (Figure 1i). We use electron probe microanalysis to quantify four main components in VMT, namely SiO 2 , MgO, Al 2 O 3 , and FeOT, and their content is found to be 39.35 ± 1.29, 24.42 ± 0.99, 10.99 ± 1.24, and 6.63 ± 0.99 wt%, respectively (Table S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The observed in‐plane distances for 2D VMT are shown in Table S1 (Supporting Information) and consistent with the atomic structure expected for monoclinic alluminosilicates. [ 27,28 ]…”
Section: Resultsmentioning
confidence: 99%